PENGARUH PENGETAHUAN DEWAN TENTANG ANGGARAN TERHADAP PENGAWASAN KEUANGAN DAERAH (APBD) DENGAN POLITICAL BACKGROUND, AKUNTANBILITAS PUBLIK DAN TRANSPARANSI KEBIJAKAN PUBLIK SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada DPRD Kabupaten Pelalawan) - Elsi Arianti; Ria Nelly Sari; Supriono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine the Council Influence Knowledge of the Financial Supervision Budget (APBD) Backgrounds Politics, Accountability, Transparency as moderating variable on all members of Parliament in the area Palalawan. Using survey data from 35 questionnaires distributed, which can be processed is 33 questionnaire. used multiple linear regression analysis with SPSS 20.0. Data analysis techniques to test hypotheses using multiple linear regression analysis approach. Hypothesis testing results show that the understanding of accounting, The results show that there is a significant negative influence between knowledge of the board of the Financial Supervision budget (APBD) the statistical value of 0,017. use political backgrounds have knowledge about the effect of the relationship between the budget and the Financial Supervision (Budget) in 0,016. And the use of statistical values of accountability has the effect of knowledge of the relationship between the budget and the Financial Supervision (APBD) in the 0,030 statistical value, transparency has no effect relationship between knowledge about the budget and the Financial Supervision (APBD) in the 0,584 statistical value.Keywords: Controller, Knowledge, Political Background, Accountability, and Transparency.